Exploring urinary biomarkers for the diagnosis of diabetic and hypertensive chronic kidney disease: A promising pilot study - Saseevan, S.; Nishanthi, N.; Sanath, R.; Magana-Arachchi, D. (Indian Journal of Experimental Biology, 2024)
In the current clinical setting, conventional serum biomarkers such as serum creatinine (Scr) and estimated glomerular filtration rate (eGFR) have several lapses in chronic kidney disease (CKD) diagnosis. Diagnosing CKD using non-invasive methods is crucial for implementing prompt therapeutic interventions and preventing disease progression. This study aims to identify the potential diagnostic urinary biomarkers and their correlation with existing renal markers, Scr, eGFR, and proteinuria in diabetic and hypertensive CKD. RNA was extracted from eighty-two urine samples of CKD patients and healthy controls (HC) and reverse transcribed for gene expression analysis using quantitative polymerase chain reactions. The expression of NGAL, MMP9, ANXA3, OLFM4, PI3, and PRMT3 genes was analyzed relative to the reference gene, B2M. Fold changes (FC) in gene expression in diabetic nephropathy (DN), and hypertensive nephropathy (HT) were calculated against HC. Log2 normalized FC was used to determine significance levels and correlation with existing serum markers. NGAL, ANXA3, and OLFM4 exhibited the highest upregulations in DN with mean Log2FC 1.42, 2.66, and 5.87, respectively. A two-fold increase in NGAL FC was observed in early DN than in late DN, suggesting its potential as an early urinary biomarker for DN. PI3 and MMP9 were upregulated in HT patients with higher FC values. PRMT3 showed a significant negative correlation (P<0.05) in HT patients with Scr (r=−0.738) and proteinuria (r=−0.906). The gene panels including ANXA3, OLFM4, and NGAL, and PI3, PRMT3, and MMP9, could have potential diagnostic value in DN and HT, respectively.
Keywords: Gene expression analysis; Non-invasive diagnosis; RT-qPCR (Reverse transcription quantitative polymerase chain reaction); Serum biomarker